"Studi Kualitatif tentang Tingkat Kepuasan Pasien Home Care di Jawa Barat: Evaluasi Layanan, Tantangan, dan Harapan ke Depan" - Bugie Zurisdianto Pamungkas; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
This study aims to evaluate the level of patient satisfaction with home care services in West Java. The research method used is qualitative study with survey and face-to-face techniques on 10 home care patients and 10 patient families in West Java. The results of the study showed that patients and patient families were very satisfied with the home care services because they provided comfort and fulfilled patient needs. In addition, healthcare workers who worked in the field of home care felt connected and useful in providing personal care focused on the patient. However, the study also identified several challenges in home care services, such as coordination between healthcare workers and families, as well as accessibility and quality of home care services. Therefore, support and cooperation from various parties, such as patient families, the community, and the government, are needed to improve the quality of home care services and ensure that patients receive the best care at home.